GROUND FLASH DENSITY OF THE BRASS COAST OF NIGERIA - Afa, John Tarilanyo; Kelvin, Benjamin Ayebapreye (European Scientific Journal, ESJ, 2013)
With the present industries and the expected industrial growth in the Brass Coast, it was necessary to study the ground flash density in the area. It is a lightning prone area because of the location and the environmental conditions. Data for thunderstorm days in the year was collected from 2008 to 2012 from the meteorological department of the oil company and meteorological department of the College of Education Okpoma. Several observations were compared and the data were analysed. The ground falsh density was found for each year in the two locations. The ground flash density (GFD) was about 10 flashes/km2/year to 15 flashes/km2/year. This data is necessary because it will help Electrical and Telecommunication Engineers and operators to involve safer and better methods to protect and minimize danger to life and equipment.